Extractive industries: addressing transparency, corruption, and theft - Tony Addison; Alan Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This paper analyses the roles that states, civil society, and international actors can play in tackling the weak governance that sometimes leads to resources being used for private rather than public benefit. It discusses the corruption that bedevils licensing and commodities trading; and oil theft which runs into billions of dollars. Ensuring transparency in revenue flows to the state is vital to better fiscal management, building governmental accountability to citizens, and to avoiding state fragility. Initiatives such as the Extractives Industries Transparency Initiative (EITI) have already achieved much, not least in improving the information base. Although corruption and theft may never be fully eliminated, they can certainly be reduced by building improved technical capacity in domestic regulation; by enhancing civil society' capacity to cast light on the sector (though dangerous work in authoritarian societies); and by strengthening transparency in supply-chains (in which information technology offers new opportunities).
Keywords: L71; L72; K42; O55; 330; commodities; corruption; extractive industries; mining; natural gas; oil